Chemical study of the strain Cordyceps spp. from cell fusion between Cordyceps militaris and Cordyceps cicadae. Issue 5 (4th May 2019) - Yang, Ning-Ning; Jiang, Ning; Ma, Qing-Yun; Kong, Fan-Dong; Xie, Qing-Yi; Zhou, Li-Man; Yu, Zhi-Fang; Zhao, You-Xing
Abstract: Chemical investigation on the cultures of the fungus Cordyceps spp., a strain from cell fusion between Cordyceps militaris and Cordyceps cicadae, resulted in the isolation of 13 compounds including 2 new ones named 2-(5-(3-oxobutyl) furan-2-yl) acetic acid (1 ) and cordycepone (2 ). Their structures were elucidated from the analysis of 1D/2D NMR and CD data. Among them, compounds 1, 7–9, at a concentration of 50 μg/ml, showed weak inhibitory activity against AChE. Moreover, compounds 6, 9, and 11 showed moderate inhibitory activity against the nematode Panagrellus redivivus with mortality ratio of 79.0, 71.7, and 72.3% at 2.5 mg/ml, respectively. Abstract :